1988
DOI: 10.1159/000275996
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunology – With Special Reference to Specific Immune Defence of the Upper Respiratory Tract

Abstract: The mucosa of the upper respiratory tract is protected by a secretory immune system which is under complex immunoregulatory control. B cells with a potential for J-chain expression are initially stimulated in mucosa-associated lymphoid tissue (probably including the tonsils) and thereafter migrate through lymph and blood to glandular sites where they differentiate to immunoglobulin-producing immunocytes. Most locally produced immunoglobulin normally consists of dimeric IgA which is selectively transported thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In nonimmunized mice IgA was located mainly in areas lined by respiratory epithelium, in the basal pole of the seromucous acini, and in the cylindrical epithelial cells, whereas scarce IgA was located in the lamina propria and basal membrane of the olfactory epithelium. It has been reported that in the respiratory mucosa the IgA is transported by transcytosis across epithelial cells and glandular epithelial cells by means of the polymeric immunoglobulin receptor (plgR) (22–28). In the olfactory mucosa of human beings and rats, the polymeric IgA and IgM are transported by epithelial cells of the Bowman's glands (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In nonimmunized mice IgA was located mainly in areas lined by respiratory epithelium, in the basal pole of the seromucous acini, and in the cylindrical epithelial cells, whereas scarce IgA was located in the lamina propria and basal membrane of the olfactory epithelium. It has been reported that in the respiratory mucosa the IgA is transported by transcytosis across epithelial cells and glandular epithelial cells by means of the polymeric immunoglobulin receptor (plgR) (22–28). In the olfactory mucosa of human beings and rats, the polymeric IgA and IgM are transported by epithelial cells of the Bowman's glands (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the glandular formation in the foetal larynx was incomplete and only immature glandular buds were detected. IgA, to which the secretory component binds and is secreted as secretory IgA via the serous-type glandular cell to function against untoward stimuli (8,9), has rarely been found in prenatal infant (10). Postnatally, the mucosal immune system begin to take place mainly at the glandular epithelium, acini.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the foetal larynx, immature glandular buds are sparsely distributed in a relatively thick subglottic mucosa (5). In the larynx of infants, the glandular acini in the mucosa tend to be sparse (11) and the mucosa is relatively thick and the inner cavity of the subglottic larynx is rather narrow (9). Nevertheless, the development of the glandular immune system of the human larynx after the birth has yet to be clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in immunology and immunopathology have revealed that the larynx possesses an active mucosal immune system as in other respiratory and digestive organs. 1,2 We have been studying the development of the mucosal defence system by glandular tissue in the human adult 3,4 and infant 5 larynx. In particular, attention has been focused on the development of laryngeal glands before and after birth.…”
Section: Introductionmentioning
confidence: 99%